2018
DOI: 10.3389/fnins.2018.00001
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuron Survival and Outgrowth on Graphene

Abstract: Graphene displays properties that make it appealing for neuroregenerative medicine, yet its interaction with peripheral neurons has been scarcely investigated. Here, we culture on graphene two established models for peripheral neurons: PC12 cells and DRG primary neurons. We perform a nano-resolved analysis of polymeric coatings on graphene and combine optical microscopy and viability assays to assess the material cytocompatibility and influence on differentiation. We find that differentiated PC12 cells display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
227
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(249 citation statements)
references
References 57 publications
22
227
0
Order By: Relevance
“…No significant influence of household preferences in the higher food aversion in ASD group than sibling groups Thullen 2017 43 62% of participants report at least one FS behavior as problematic.No significant association between FS and parenting stress. Association between child disruptive behavior at mealtime and quality of co-parenting ( p <0.05) Berding 2018 17 Lower rate of exclusive breastfeeding (20%, p<0.05) Higher percentage of children eating less than 20 foods (54%, p <0.05). No differences in picky eating and repetitive eating pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant influence of household preferences in the higher food aversion in ASD group than sibling groups Thullen 2017 43 62% of participants report at least one FS behavior as problematic.No significant association between FS and parenting stress. Association between child disruptive behavior at mealtime and quality of co-parenting ( p <0.05) Berding 2018 17 Lower rate of exclusive breastfeeding (20%, p<0.05) Higher percentage of children eating less than 20 foods (54%, p <0.05). No differences in picky eating and repetitive eating pattern.…”
Section: Resultsmentioning
confidence: 99%
“… 17 , 20 , 33 , 34 , 36 , 34 , 42 – 49 Most studies found a higher prevalence of FS in ASD children compared with TD controls. 17 , 32 , 36 , 40 50 – 56 However, one study found that a difference between ASD and TD children exists only when considering severe eating selectiveness, while no difference emerged about EP of mild severity. 41…”
Section: Resultsmentioning
confidence: 99%
“…Convertino presented a surface analysis with PLL, PDL and collagen layers, performed by atomic force microscope. Polylysine modified surface is more homogeneous, while network aggregates can be observed in the collagen coating [45]. Therefore, it can be assumed that the heterogeneity of the surface affects the stronger attachment of cells to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…How cannabinoids modulate neurogenesis in physiological, epileptic, and other pathological conditions (in both in vitro and in vivo) is further reviewed in References [ 43 , 243 , 251 , 252 ].…”
Section: Cannabinoids and The Endocannabinoid Systemmentioning
confidence: 99%